Nigella sativa improves glycemic control and ameliorates oxidative stress in patients with type 2 diabetes mellitus: placebo controlled participant blinded clinical trial. - Huda Kaatabi; Abdullah Omar Bamosa; Ahmed Badar; Abdulmohsen Al-Elq; Bodour Abou-Hozaifa; Fatma Lebda; Akram Al-Khadra; Sameeh Al-Almaie (PLoS ONE)
Background and objective Oxidative stress plays an important role in pathogenesis of diabetes mellitus and its complications. Our previous study has shown glucose lowering effect produced by 3 months supplementation of Nigella sativa (NS) in combination with oral hypoglycemic drugs among type 2 diabetics. This study explored the long term glucose lowering effect (over one year) of NS in patients with type 2 diabetes mellitus on oral hypoglycemic drugs and to study its effect on redox status of such patients. Methods 114 type 2 diabetic patients on standard oral hypoglycemic drugs were assigned into 2 groups by convenience. The control group (n = 57) received activated charcoal as placebo and NS group (n = 57) received 2g NS, daily, for one year in addition to their standard medications. Fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), C- peptide, total antioxidant capacity (TAC), superoxide dismutase (SOD), catalase (CAT), glutathione and thiobarbituric acid reactive substances (TBARS) at the baseline, and every 3 months thereafter were determined. Insulin resistance and β-cell activity were calculated using HOMA 2 calculator. Results Comparison between the two groups showed a significant drop in FBG (from 180 ± 5.75 to 180 ± 5.59 in control Vs from 195 ± 6.57 to 172 ± 5.83 in NS group), HbA1c (from 8.2 ± 0.12 to 8.5 ± 0.14 in control VS from 8.6 ± 0.13 to 8.2 ± 0.14 in NS group), and TBARS (from 48.3 ± 6.89 to 52.9 ± 5.82 in control VS from 54.1 ± 4.64 to 41.9 ± 3.16 in NS group), in addition to a significant elevation in TAC, SOD and glutathione in NS patients compared to controls. In NS group, insulin resistance was significantly lower, while β-cell activity was significantly higher than the baseline values during the whole treatment period. Conclusion Long term supplementation with Nigella sativa improves glucose homeostasis and enhances antioxidant defense system in type 2 diabetic patients treated with oral hypoglycemic drugs. Trial registration Clinical Trials Registry-India (CTRI) CTRI/2013/06/003781.